2010
DOI: 10.1007/s10900-010-9308-8
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Screening of Adolescent Females: A Survey of Providers in Hawaii

Abstract: Hawaii currently ranks first among states for chlamydia screening of young women based on recent Healthcare Effectiveness Data and Information Set (HEDIS) measures and has consistently ranked in the top ten states in the US for annual reported chlamydia rates since 2002. A statewide provider survey was conducted in October 2007 and March 2008 to assess chlamydia screening practices and beliefs and identify potential barriers to screening. The overall reported screening rate for 15-19 year old females was 66.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[30] An evaluation of the HEDIS chlamydia measure among providers in Hawaii found that a lack of awareness of reimbursement for screening was a barrier to following the recommendation. [31] Finally, it is possible that some policy changes do not have an impact on screening. For instance, changes in insurance coverage for chlamydia screening in two states did not appear to impact screening rates [32]; and, syphilis screening among pregnant women has remained low even in an area of high incidence.…”
Section: Policies Focused On Std Prevention Issuesmentioning
confidence: 99%
“…[30] An evaluation of the HEDIS chlamydia measure among providers in Hawaii found that a lack of awareness of reimbursement for screening was a barrier to following the recommendation. [31] Finally, it is possible that some policy changes do not have an impact on screening. For instance, changes in insurance coverage for chlamydia screening in two states did not appear to impact screening rates [32]; and, syphilis screening among pregnant women has remained low even in an area of high incidence.…”
Section: Policies Focused On Std Prevention Issuesmentioning
confidence: 99%
“…These same trends are observed among Hawai‘i youth. Since 2002, Hawai‘i has ranked consistently in the top 10 states in chlamydia rates (McGrath, Katz, Lee, & Rochat, 2011), particularly among those aged 15 to 24 years. In 2004, 63% of reported cases of chlamydia and 50% of gonorrhea cases in Hawai‘i were among people in this age group (Advocates for Youth, 2008).…”
Section: Introductionmentioning
confidence: 99%